2018
DOI: 10.1111/jwas.12513
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Contribution of Biofloc within the Diet of Growout and Broodstock of Litopenaeus vannamei, Determined by Stable Isotopes and Fatty Acids

Abstract: The relative contributions of feed sources were determined through the isotopic signal ( 13 C and 15 N) and fatty acid profile of feed items, shrimp muscle, and eggs of Litopenaeus vannamei reared in a biofloc system. In the growout phase, the isotope analysis showed the biofloc particle size class ≥250 m contributed 55-100%; size ≥50 < 250 m contributed 0-22%; and artificial feed contributed 0-45%. Principal component analysis applied to fatty acid profiles showed that biofloc ≥250 m and artificial feed were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…In general, microbial aggregates offer a supplemental source of proteins and lipids (Bakhshi et al, 2018). However, important nutrients for shrimp, such as methionine and lysine, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are observed at low levels in microbial flocs (Hu et al, 2011; Magaña‐Gallegos et al, 2018; Zhou et al, 2007). Thus, some studies have shown that the addition of microorganisms to shrimp culture can improve zootechnical performance, probably due to the proximal composition of the microbial flocs (Abreu et al, 2019; Brito et al, 2016; Jamali et al,2015; Marinho et al, 2014, 2017; Martins et al, 2016) and also digestive enzymes and bioactive compounds (Shah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, microbial aggregates offer a supplemental source of proteins and lipids (Bakhshi et al, 2018). However, important nutrients for shrimp, such as methionine and lysine, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are observed at low levels in microbial flocs (Hu et al, 2011; Magaña‐Gallegos et al, 2018; Zhou et al, 2007). Thus, some studies have shown that the addition of microorganisms to shrimp culture can improve zootechnical performance, probably due to the proximal composition of the microbial flocs (Abreu et al, 2019; Brito et al, 2016; Jamali et al,2015; Marinho et al, 2014, 2017; Martins et al, 2016) and also digestive enzymes and bioactive compounds (Shah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of bioflocs in feed nutrient utilization, and the growth and health of the cultured organism would depend on the organism's capabilities to consume and utilize nutrients deriving from bioflocs. The ability of an aquaculture organism in consuming bioflocs is determined by at least two factors, that is the morphological structure of the animal in particular that relate to feeding activities (Kim et al, 2015) and the size of biofloc particles (Ekasari, Angela, et al, 2014; Fatimah et al, 2019; Magaña‐Gallegos et al, 2018). The present study confirms that the addition of microalgae could increase the size of biofloc particles; however, it is not clear whether this brings about some benefits for the giant prawn.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms that the addition of microalgae could increase the size of biofloc particles; however, it is not clear whether this brings about some benefits for the giant prawn. A study on Pacific white shrimp, for instance, demonstrated that based on the fatty acid profiles, and δ 13 C and δ 15 N isotope analyses, biofloc with a size of >250 μm was one of the most important food items in shrimp growout culture (Magaña‐Gallegos et al, 2018). Kim et al, (2015) noted that the longer seta and smaller distance between seta of the third maxilliped endopods in Pacific white shrimp allowed higher efficiency in filtering and capturing of the suspended bioflocs.…”
Section: Discussionmentioning
confidence: 99%
“…The biofloc rearing system has been developed to implement the use of minimum water exchange in aquaculture ponds, producing heterotrophic media and a multiphasic feed source (Avnimelech, ; Magaña‐Gallegos et al, ), which improve the nutritional and reproductive performances of shrimp (Emerenciano, Gaxiola, & Cuzon, ). Because of the minimum water exchange, it has been suggested that biofloc prevents pathogen entry ponds and disease outbreak expansion between farms (Crab, Lambert, Defoirdt, Bossier, & Verstraete, ).…”
Section: Introductionmentioning
confidence: 99%